Evaluation of spin-transfer-torque efficiency using magnetization reversal against a magnetic field: comparison of FeCr with negative spin polarization and NiFe. (1st January 2023) - Suto, Hirofumi; Nakatani, Tomoya; Asam, Nagarjuna; Iwasaki, Hitoshi; Sakuraba, Yuya
Abstract: We propose and demonstrate an experimental method to evaluate spin-transfer-torque (STT) efficiency in current-perpendicular-to-plane giant magnetoresistance devices, which utilizes STT-induced magnetization reversal against a perpendicular magnetic field. Using this method, we estimated the STT efficiency of FeCr with negative spin polarization, which attracts attention in spintronics applications. In comparison with NiFe with positive spin polarization, the sign of the STT induced by FeCr was opposite, reflecting the negative spin polarization. The STT efficiency of FeCr was approximately half that of NiFe at room temperature and surpassed that of NiFe at 50 K.